2019
DOI: 10.3390/cancers11091250
|View full text |Cite
|
Sign up to set email alerts
|

Immune Heterogeneity Between Primary Tumors and Corresponding Metastatic Lesions and Response to Platinum Therapy in Primary Ovarian Cancer

Abstract: CD3+ and CD8+ lymphocytes are well known prognostic markers in primary ovarian cancer. In contrast, the predictive value of the immune infiltrate concerning treatment response and the involvement of immune heterogeneity between primary and metastatic lesions are poorly understood. In this study, the immune infiltrate of 49 primary tumors and 38 corresponding lesions in the omentum (n = 23) and the peritoneum (n = 15) was immunohistochemically analyzed and correlated with clinicopathological factors and platinu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 53 publications
2
9
0
Order By: Relevance
“…We thus showed for the first time that the percentages of CD8, PD-1, and PD-L1 expressing subpopulations of TILs differ in primary ovarian tumor tissues and metastatic intraperitoneal tumor implants. Our findings complement recently published data on a significantly higher number of tumor infiltrating CD8 positive as well as a lower number of PD-1 positive immune cells in metastatic compared to primary lesions 13 . Additionally, in line with several previously published studies 14 17 our results confirm the favorable prognosis in patients with higher levels of tumor infiltrating CD8 + T cells in ovarian cancer tissue.…”
Section: Discussionsupporting
confidence: 92%
“…We thus showed for the first time that the percentages of CD8, PD-1, and PD-L1 expressing subpopulations of TILs differ in primary ovarian tumor tissues and metastatic intraperitoneal tumor implants. Our findings complement recently published data on a significantly higher number of tumor infiltrating CD8 positive as well as a lower number of PD-1 positive immune cells in metastatic compared to primary lesions 13 . Additionally, in line with several previously published studies 14 17 our results confirm the favorable prognosis in patients with higher levels of tumor infiltrating CD8 + T cells in ovarian cancer tissue.…”
Section: Discussionsupporting
confidence: 92%
“…Some studies have focused on the differences in CD8 TILs between the primary and metastatic sites, but have only shown differences in the degree of CD8 infiltration, or in the CD8/CD3 ratio among infiltrating lymphocytes. 55 56 Due to our insufficient knowledge regarding CD8 TILs at metastatic sites, current clinical or laboratory use of immunotherapy has been based on the assumption that the immunological characteristics of exhausted CD8 TILs would be similar between the metastatic and primary sites—and that if there was a difference, the CD8 TILs in metastatic sites would be less exhausted than those in the primary sites. Notably, our present results suggested that CD39 + CD8 TILs from the metastatic sites and primary sites of ovarian cancer exhibited similar exhaustion status, although the CD39 + CD8 TILs from metastatic sites were slightly less activated than those from the primary sites.…”
Section: Discussionmentioning
confidence: 99%
“…Serial cryosections (5 µm) were performed. The samples were stained immunohistochemically using the avidin–biotin–peroxidase method [ 24 ]. Tissue sections were fixed either in acetone for 8 min or, for the antigens ERα and PgR, in formalin for 3 min and afterwards in a citrate buffer for 7 min at 90 °C.…”
Section: Methodsmentioning
confidence: 99%
“…In the absence of standardized cut-offs for other biomarkers, cut-offs were evaluated according to the biphasic distribution or the group size (see Table 1 ). Quantitative evaluation of CD3, CD8, and PD-1, and semiquantitative evaluation of PD-L1 was performed according to Dotzer et al [ 24 ].…”
Section: Methodsmentioning
confidence: 99%